2022
DOI: 10.2298/tsci2203683c
|View full text |Cite
|
Sign up to set email alerts
|

Vapor injection technology for heat-pump air conditioner of electric bus in an extreme environment

Abstract: In order to solve the problems of a heat pump air conditioner for an electric bus under extreme conditions, such as the large compression ratio, the high discharge temperature, the reduced system performance, the frequent shutdown of the compressor due to the overheat protection, this paper proposes a vapor injection technology with an economizer, and carries out a theoretical analysis of the process to reveal the effect of the vapor injection technology on the performance of the air conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…According to the aforementioned literature, vapor injection technology can boost the heating/cooling capacity and the coefficient of performance (COP) of the refrigeration system, and it is especially suitable for applications on high-temperature heat pumps and low-temperature air conditioners [22,23]. However, for the chiller application, due to the low temperature rise, the injection pressure difference is low, and the injection port is also small because of the limited compressor surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the aforementioned literature, vapor injection technology can boost the heating/cooling capacity and the coefficient of performance (COP) of the refrigeration system, and it is especially suitable for applications on high-temperature heat pumps and low-temperature air conditioners [22,23]. However, for the chiller application, due to the low temperature rise, the injection pressure difference is low, and the injection port is also small because of the limited compressor surface.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [29] proposed an improved CO 2 heat pump system for electric vehicles by introducing the concept of two-stage compression with intermediate cooling and conducted experiments between the two-stage compression heat pump and the basic heat pump. The results showed that compared with the basic single-stage cycle system, the heating capacity and COP of the two-stage compression system were increased by 50-132% and 18.9-61.9%, respectively, as the ambient temperature decreased from 0 • C to −20 • C. Ning et al [30] proposed a multifunctional two-stage vapor compression heat pump air conditioning system with its operation strategies, which can operate not only in a single-stage vapor compression cooling and heating mode, but also in a two-stage vapor compression heating mode under ambient temperatures as low as −35 • C. According to the aforementioned literature, vapor injection technology can boost the heating/cooling capacity and the coefficient of performance (COP) of the refrigeration system, and it is especially suitable for applications on high-temperature heat pumps and low-temperature air conditioners [22,23]. However, for the chiller application, due to the low temperature rise, the injection pressure difference is low, and the injection port is also small because of the limited compressor surface.…”
Section: Introductionmentioning
confidence: 99%